Innovations in Social Studies Learning Based on Deep Learning in Developing Students’ Critical Thinking Skills - Muh. Abid Mustahar. AM; Alimin Alwi; Najamuddin; Supriadi Torro (International Journal of Technology and Education Research, 2026)
This article aims to examine innovations in Social Studies learning based on deep learning in developing students’ critical thinking skills. This study employs a library research method by collecting and analyzing various relevant scientific sources, including journal articles, books, and educational policy documents. Data analysis was conducted using content analysis techniques to identify key themes related to the concept of deep learning, the characteristics of Social Studies learning, and its role in fostering critical thinking. The findings indicate that the deep learning approach emphasizes meaningful learning, active student engagement, and reflection on learning experiences, which aligns with the contextual and socially grounded nature of Social Studies education. The integration of deep learning in Social Studies can be implemented through instructional models such as project-based learning and inquiry learning, which promote analysis, exploration, and problem-solving of social issues. This approach has been shown to contribute to the enhancement of critical thinking skills through strengthening conceptual understanding, information analysis, and reflective processes. However, its implementation still faces several challenges, including limited teachers’ digital literacy, pedagogical readiness, technological infrastructure, and a learning culture that remains oriented toward rote memorization. Therefore, comprehensive support from multiple aspects is required to optimize the implementation of deep learning in Social Studies learning in the digital era.